Tire curing bladder based on nano material and preparation method thereof

Through the preparation method based on nanomaterials, the problems of short service life and slow vulcanization speed in high-temperature and high-humidity environments were solved, and high-strength, high-wear-resistant tire vulcanization capsules were prepared, achieving uniform dispersion of materials and efficient vulcanization. , improves production efficiency and finished product quality.

CN119176993AInactive Publication Date: 2024-12-24SHANDONG YONGYU RUBBER CO LTD

Patent Information

Application Number
CN202411230909.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing tire vulcanized capsules have short service life and slow vulcanization speed in high temperature and high humidity environments, which affects production efficiency, and uneven dispersion of materials affects comprehensive performance.

Method used

Using a nanomaterial-based preparation method, the butyl rubber, modified butyl chloride rubber, modified composite resin, magnesium oxide, accelerator, softener, anti-coke agent and processing auxiliary agent are kneaded at high temperature. High-strength, high wear-resistant tire vulcanization capsules were prepared through injection vulcanization process, and carbon black was coated with 3-hydroxypyridine to produce zinc oxide and acrylate modified nanosilica in situ to improve dispersion and mechanical properties.

Benefits of technology

It significantly improves the strength, wear resistance and service life of tire vulcanized capsules, ensures uniform dispersion and efficient vulcanization of materials, and improves production efficiency and finished product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of tire curing bladders, in particular to a tire curing bladder based on a nano material and a preparation method of the tire curing bladder. Butyl rubber, modified chlorinated butyl rubber, modified composite resin, magnesium oxide, an accelerant, a softening agent, an anti-scorching agent and a processing aid are used as raw materials, the tire curing bladder is prepared through an injection molding process after mixing and tabletting, carbon black is modified, zinc oxide and nano silicon dioxide are introduced through an in-situ generation method, and the tire curing bladder is prepared. Therefore, the mechanical property of the prepared product is effectively improved, and the prepared product has a relatively long service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tire vulcanization bladders, and in particular to a tire vulcanization bladder based on nano materials and a preparation method thereof. Background Art

[0002] Curing bladder is an indispensable auxiliary material for tire production. It is a large rubber product among rubber products and a consumable in the tire manufacturing industry. Whether high-quality tires can be produced depends largely on the quality of the curing bladder, because the curing bladder is the most important tool for vulcanizing the tire outer casing. Its quality not only affects the number of times it is used, which is related to the cost of tire production, but also affects the quality and service life of the finished tire. During the tire vulcanization process, the medium can be transferred to the tire through the curing bladder, providing the heat required for vulcanization, while ensuring that the tire has a reasonable inner contour shape. Due to the conditions required by the curing bladder during use, the selection of rubber is very demanding. It is required that the rubber must be able to be used in a high temperature, high humidity and high pressure environment for a long time. Therefore, the use of rubber has high requirements. The commonly used rubber is butyl rubber, but the high saturation of butyl rubber makes it have the disadvantage of slow vulcanization speed during the vulcanization process, which affects the production efficiency of the factory.

[0003] Patent CN101775175B discloses a tire vulcanization bladder made of nano silicon-based oxide and a preparation process. By introducing nano silicon-based oxide, the heat aging resistance of the prepared material is effectively improved, the permanent deformation of the rubber material is reduced, and the service life of the tire vulcanization bladder is improved. In addition, in the preparation process, nano silicon-based oxide is first added to the raw rubber at the beginning of mixing to ensure that it has a good combination with the rubber, and a secondary mixing process is added to meet the production process requirements and the dispersion effect is ideal; Patent CN105647038B discloses a preparation method for a high-strength tire vulcanization bladder, which is obtained by modifying butyl rubber and selecting a multi-component composite ternary vulcanization system to strictly screen the conditions of the preparation process. A tire vulcanization bladder with high strength and good weather resistance is obtained. However, in the above preparation process, the raw materials are directly mixed, which easily causes uneven dispersion of the materials, thereby affecting its comprehensive performance. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a nano-material-based tire vulcanization bladder and a preparation method thereof, wherein butyl rubber, modified chlorinated butyl rubber, modified composite resin, magnesium oxide, accelerator, softener, scorch retarder and processing aid are mixed at high temperature and then subjected to an injection vulcanization process to obtain a tire vulcanization bladder with high strength and high wear resistance.

[0005] To solve the above problems, the technical solution provided by the present invention is: A method for preparing a tire curing bladder based on nanomaterials comprises the following steps: S1. Under an inert atmosphere, blending chlorobutyl rubber with modified carbon black and zinc oxide composite, and mixing at 85-110° C. for 10-20 min to obtain modified chlorobutyl rubber; wherein the inert atmosphere is a nitrogen atmosphere, and the mass ratio of chlorobutyl rubber to modified carbon black and zinc oxide composite is 35-45:38-52; S2, mixing the brominated alkylphenol-formaldehyde resin and the acrylate-modified nano-silica uniformly to obtain a modified composite resin; wherein the mass ratio of the brominated alkylphenol-formaldehyde resin to the acrylate-modified nano-silica is 10-12:5-8; S3, blending butyl rubber, modified chlorobutyl rubber, modified composite resin, magnesium oxide, accelerator, softener, scorch retarder and processing aid, mixing at 95-125° C. for 20-40 min, and pressing into sheets to obtain mixed sheets after mixing; wherein the mass ratio of butyl rubber, modified chlorobutyl rubber, modified composite resin, magnesium oxide, accelerator, softener, scorch retarder and processing aid is 32-38:52-60:20-25:1-1.8:2.2-3:2-3:1.2-2.4:1-2; S4. Put the mixed rubber sheet into an injection vulcanizer, control the screw temperature at 75-85°C, the pressure at 18-22MPa, the injection vulcanization temperature at 180-220°C, and injection vulcanize for 35-45 minutes to obtain a tire vulcanization bladder.

[0006] Furthermore, in step S1, the preparation method of the modified carbon black and zinc oxide composite is: A1. Dissolve 3-hydroxypyridine in isopropanol under an inert atmosphere, add carbon black thereto, and stir at room temperature for 15-25 min to obtain a mixed solution 1; wherein the inert atmosphere is a nitrogen atmosphere; the amount of 3-hydroxypyridine in isopropanol is 0.12-0.22 g / mL, the mass ratio of 3-hydroxypyridine to carbon black is 1:10-15, and the carbon black is a mixture of carbon black N220 and carbon black N550 in a mass ratio of 1:1; In this step, when the butyl rubber material is prepared, the use of carbon black can effectively improve the physical and mechanical properties of the rubber product. However, since it contains a large number of groups and has a high surface activity, and the surface energy of the high molecular polymer is low, the dispersion of carbon black in the rubber material is poor. Therefore, in the present invention, 3-hydroxypyridine is used to coat the carbon black to obtain modified carbon black. By modifying the surface of the carbon black and introducing groups such as hydroxyl groups and pyridine rings, the dispersion of the carbon black is facilitated. A2, zinc chloride is added to deionized water, dilute hydrochloric acid is added dropwise under stirring to obtain a colorless transparent solution, and sodium hydroxide solution is added dropwise thereto to adjust the solution pH to 8 to obtain a white precipitate, which is washed with deionized water and mixed with a polyvinylpyrrolidone aqueous solution to obtain a mixed solution 2; wherein the amount of zinc chloride in deionized water is 0.2-0.25 g / mL, the concentration of dilute hydrochloric acid is 1 mol / L, the concentration of sodium hydroxide solution is 2 mol / L, the amount of polyvinylpyrrolidone in the polyvinylpyrrolidone aqueous solution is 0.25-0.3 g / mL, and the mass ratio of zinc chloride to polyvinylpyrrolidone is 1:1.2-2.2; In this step, since the unsaturation degree of butyl rubber is extremely low, its vulcanization is relatively difficult, requiring not only a stronger vulcanization system, but also a higher vulcanization temperature and a longer vulcanization time; therefore, in the present invention, a brominated alkylphenol formaldehyde resin vulcanization system with excellent high temperature resistance is used for vulcanization, in which the addition of zinc oxide can effectively increase the vulcanization speed, but due to its high surface activity, direct addition of zinc oxide is very likely to cause agglomeration, so in the present invention, zinc oxide is introduced into the reaction system by an in-situ generation method, firstly, zinc chloride is dissolved in a hydrochloric acid solution, then the pH value of the solution is adjusted with a sodium hydroxide solution to obtain a large amount of zinc hydroxide precipitation, then polyvinyl pyrrolidone is added to achieve coating of the zinc hydroxide particles, and finally, in the mixing process, zinc oxide particles are generated in-situ under the action of high temperature; in the zinc oxide generation process, complex coordination bonds and other interactions are formed between polyvinyl pyrrolidone and zinc ions, thereby reducing the collision probability between zinc oxide particles, and at the same time, the presence of polymer chains in polyvinyl pyrrolidone can provide a large steric hindrance, so that they repel each other and reduce agglomeration, thereby being in a highly dispersed state; A3. Under stirring in an inert atmosphere, add the mixed solution 1 dropwise to the mixed solution 2, add a silane coupling agent thereto after the addition is completed, and stir for 20-30 minutes to obtain a modified carbon black and zinc oxide composite; wherein the inert atmosphere is a nitrogen atmosphere, and the silane coupling agent is at least one of KH550, KH560, and KH570, preferably KH550; the mass ratio of the silane coupling agent to the carbon black in step A1 is 0.1:16-24; and the volume ratio of the mixed solution 1 to the mixed solution 2 is 8:1.

[0007] The silane coupling agent is reactive to inorganic substances, and the organic functional group is reactive or compatible to organic substances. Therefore, in the present invention, the silane coupling agent is added between the modified carbon black and the zinc hydroxide coated with polyvinyl pyrrolidone to form a combination of an organic matrix of zinc hydroxide coated with polyvinyl pyrrolidone-silane coupling agent-an inorganic matrix of modified carbon black; in the further vulcanization process, the hydroxyl groups contained on the surface of the modified carbon black separate the -Cl in the chlorobutyl rubber in the form of hydrogen chloride through vulcanization, thereby combining the combination containing the modified carbon black with the chlorobutyl rubber; in addition, the positively charged pyridine ring contained in the combination and the free chloride ions are aggregated together through positive and negative charges to form an ion cross-linking network, which can effectively improve the mechanical properties of the chlorobutyl rubber, and the mobility of the molecular chain is increased at high temperature, so that the prepared rubber composite material has a certain fluidity, and has a certain repair effect on the damaged parts generated during use, thereby effectively extending the service life of the prepared product.

[0008] Further, in step S2, the preparation method of acrylate-modified nano-silica is as follows: at 25-35° C., cetyltrimethylammonium bromide, anhydrous ethanol and ammonia water are added to deionized water, stirred for 40-60 minutes, and then tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and methyl methacrylate mixture are added thereto, stirred at 35-45° C. for 18-24 hours, and centrifuged and dried to obtain; wherein the amount of cetyltrimethylammonium bromide in deionized water is 0.0 12-0.015g / mL, the volume ratio of deionized water, anhydrous ethanol and ammonia water is 20-25:60-65:1, the mass ratio of hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and methyl methacrylate is 0.2-0.6:8-12:1-1.5:4-5; the centrifugal conditions are: centrifugal speed 1000-1500rpm for 30-40min, and the drying conditions are: drying in a vacuum drying oven at 30-45℃ for 6-8h.

[0009] The volume effect and quantum tunneling effect of nano silicon dioxide make it penetrate deeply into the π bond of the polymer compound, overlap with the electron cloud of the polymer compound, and form a spatial network structure, thereby greatly improving the mechanical strength, toughness, wear resistance and other properties of the polymer material. However, the compatibility of nano silicon dioxide with the matrix is ​​poor, thereby affecting the filling effect of the material. Therefore, in the present invention, methyl methacrylate is introduced in the preparation process to coat the generated nano silicon dioxide, and the hydrophilic group of the monomer produces a condensation reaction with the silanol group on the surface of the nano silicon dioxide, and the vinyl group of the lipophilic part can produce a condensation reaction with the double bond in the rubber material, which is beneficial to the dispersion of the nano silicon dioxide. In addition, the surface of the nano silicon dioxide prepared by the precipitation method of the present invention contains silanol groups and hydroxyl groups. Through the coating of acrylate, the adverse effects of the silanol groups and hydroxyl groups on the surface of the nano silicon dioxide on vulcanization can be avoided. In addition, acrylate has unsaturated bonds, which increases the cross-linking activity, thereby effectively improving the fatigue resistance and other properties of the tire rubber.

[0010] Furthermore, in step S3, the accelerator is at least one of accelerator DM and accelerator ZDC, the softener is sulphurized cottonseed oil, the scorch retarder is PVI, and the processing aid is stearic acid.

[0011] The present invention also provides a nano-material-based tire vulcanization bladder, which is prepared by adopting the preparation method of the nano-material-based tire vulcanization bladder.

[0012] The present invention has the following beneficial effects: The present invention uses 3-hydroxypyridine to coat carbon black to obtain modified carbon black, and introduces groups such as hydroxyl groups and pyridine rings by modifying the surface of carbon black, which is helpful for the dispersion of carbon black; in addition, zinc oxide is introduced into the reaction system by an in-situ growth method, and polyvinyl pyrrolidone is added in the generation process, which can form complex coordination bonds and other interactions with zinc ions, thereby reducing the collision probability between zinc oxide particles. At the same time, the presence of polymer chains in polyvinyl pyrrolidone can provide a large steric hindrance, so that they repel each other and reduce agglomeration, thereby being in a highly dispersed state; in addition, in the preparation of the present invention, In the process, a combination of polyvinyl pyrrolidone-coated zinc hydroxide organic matrix-silane coupling agent-modified carbon black inorganic matrix is ​​constructed. In the further vulcanization process, the hydroxyl groups contained on the surface of the modified carbon black separate the -Cl in the chlorobutyl rubber in the form of hydrogen chloride through vulcanization, thereby combining the combination containing the modified carbon black with the chlorobutyl rubber; at the same time, the positively charged pyridine ring contained in the combination and the free chloride ions are aggregated together through positive and negative charges to form an ion cross-linking network, which can effectively improve the mechanical properties and high-temperature fluidity of the chlorobutyl rubber, and effectively extend the life of the prepared product. DETAILED DESCRIPTION

[0013] The following will be combined with the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0014] The butyl rubber used in the present invention was purchased from Exxon (IIR268) of the United States, chlorobutyl rubber (CR321) was purchased from Shanghai Ruhua Chemical Technology Co., Ltd., carbon black N220 and carbon black N550 were purchased from Zhongbei Fine Chemical, brominated alkylphenol resin (HM201) was purchased from Jiangsu Qichao New Material Technology Co., Ltd., methyl methacrylate was purchased from Shantou Xilong Chemical Plant in Guangdong, magnesium oxide (analytical grade) was purchased from Tianjin Bodi Chemical Co., Ltd., stearic acid (industrial grade) was purchased from Tianjin Huanyu Rubber Co., Ltd., zinc chloride, sodium hydroxide, and HCl were all analytical reagents, polyvinyl pyrrolidone (AR), hexadecyltrimethylammonium bromide (AR), ammonia water (AR), tetraethyl orthosilicate (AR), and bis-[γ-(triethoxysilyl)propyl]-tetrasulfide (AR) were purchased from Macklin reagent, and all reagents were commercially available. Example 1

[0015] A method for preparing a tire curing bladder based on nanomaterials comprises the following steps: S1. Under a nitrogen atmosphere, chlorobutyl rubber is blended with a modified carbon black and zinc oxide composite, and kneaded at 100° C. for 15 min to obtain a modified chlorobutyl rubber; wherein the mass ratio of the chlorobutyl rubber to the modified carbon black and zinc oxide composite is 42:45; S2, mixing the brominated alkylphenol-formaldehyde resin and the acrylate-modified nano-silica uniformly to obtain a modified composite resin; wherein the mass ratio of the brominated alkylphenol-formaldehyde resin to the acrylate-modified nano-silica is 11:7; S3, blending butyl rubber, modified chlorobutyl rubber, modified composite resin, magnesium oxide, accelerator, softener, scorch retarder and processing aid, mixing at 105° C. for 35 min, and pressing into sheets to obtain mixed sheets after mixing; wherein the mass ratio of butyl rubber, modified chlorobutyl rubber, modified composite resin, magnesium oxide, accelerator, softener, scorch retarder and processing aid is 36:54:22:1.5:2.5:2.2:1.8:1.2; S4. Put the mixed rubber sheet into an injection vulcanizer, control the temperature of the screw at 85°C, the pressure at 20 MPa, the injection vulcanization temperature at 210°C, and inject vulcanize for 40 minutes to obtain a tire vulcanization bladder.

[0016] Wherein, in step S1, the preparation method of the modified carbon black and zinc oxide composite is: A1. Dissolve 3-hydroxypyridine in isopropanol under a nitrogen atmosphere, add carbon black thereto, and stir at room temperature for 18 min to obtain a mixed solution 1; wherein the amount of 3-hydroxypyridine in isopropanol is 0.18 g / mL, the mass ratio of 3-hydroxypyridine to carbon black is 1:12, and the carbon black is a mixture of carbon black N220 and carbon black N550 in a mass ratio of 1:1; A2, zinc chloride was added to deionized water, dilute hydrochloric acid was added dropwise under stirring to obtain a colorless transparent solution, and sodium hydroxide solution was added dropwise thereto to adjust the solution pH to 8 to obtain a white precipitate, which was washed with deionized water and mixed with a polyvinylpyrrolidone aqueous solution to obtain a mixed solution 2; wherein the amount of zinc chloride in deionized water was 0.22 g / mL, the concentration of dilute hydrochloric acid was 1 mol / L, the concentration of sodium hydroxide solution was 2 mol / L, the amount of polyvinylpyrrolidone in the polyvinylpyrrolidone aqueous solution was 0.28 g / mL, and the mass ratio of zinc chloride to polyvinylpyrrolidone was 1:1.8; A3. Under stirring in a nitrogen atmosphere, the mixed solution 1 was added dropwise to the mixed solution 2. After the addition was completed, a silane coupling agent KH550 was added thereto, and the mixture was stirred for 25 minutes to obtain a modified carbon black and zinc oxide composite; wherein the mass ratio of the silane coupling agent to the carbon black in step A1 was 0.1:18.

[0017] Wherein, in step S2, the preparation method of acrylate-modified nano-silica is as follows: at 30° C., cetyltrimethylammonium bromide, anhydrous ethanol and ammonia water are added to deionized water, stirred for 45 minutes, and then tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and a mixture of methyl methacrylate are added thereto, stirred at 40° C. for 20 hours, and the mixture is centrifuged and dried to obtain the acrylate-modified nano-silica; wherein the amount of cetyltrimethylammonium bromide in deionized water is 0.012 g / mL, the volume ratio of deionized water, anhydrous ethanol and ammonia water is 22:62:1, and the mass ratio of cetyltrimethylammonium bromide, tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and methyl methacrylate is 0.4:10:1.2:4.2; the centrifugal conditions are: centrifugal rotation speed 1200 rpm for 35 minutes, and the drying conditions are: drying in a vacuum drying oven at 35° C. for 6 hours.

[0018] Wherein, in step S3, the accelerator is accelerator DM, the softener is sulphurized cottonseed oil, the scorch retarder is PVI, and the processing aid is stearic acid. Example 2

[0019] Compared with Example 1, this embodiment has the following differences, and the rest is referred to Example 1, which is as follows: In the preparation process of tire curing bladder based on nanomaterials, in step S1, chlorinated butyl rubber and modified carbon black and zinc oxide composite are mixed at 85°C for 10 minutes, and the mass ratio of chlorinated butyl rubber to modified carbon black and zinc oxide composite is 35:38; in step S2, the mass ratio of brominated alkylphenol formaldehyde resin to acrylate modified nano-silica is 10:5; in step S3, butyl rubber, modified chlorinated butyl rubber, modified composite resin, magnesium oxide, accelerator , softener, scorch retarder and processing aid are mixed at 95°C for 20 minutes, and the mass ratio of butyl rubber, modified chlorobutyl rubber, modified composite resin, magnesium oxide, accelerator, softener, scorch retarder and processing aid is 32:52:20:1:2.2:2:1.2:1; in step S4, the mixed rubber sheet is placed in an injection vulcanizer, the screw temperature is controlled at 75°C, the pressure is controlled at 18 MPa, the injection vulcanization temperature is 180°C, and the injection vulcanization is carried out for 35 minutes.

[0020] In the preparation process of the modified carbon black and zinc oxide composite, in step A1, 3-hydroxypyridine is dissolved in isopropanol, carbon black is added, and the mixture is stirred at room temperature for 15 minutes, the amount of 3-hydroxypyridine in isopropanol is 0.12 g / mL, the mass ratio of 3-hydroxypyridine to carbon black is 1:10, and the carbon black is a mixture of carbon black N220 and carbon black N550 in a mass ratio of 1:1; in step A2, the amount of zinc chloride in deionized water is 0.2 g / mL, the concentration of dilute hydrochloric acid is 0. The concentration of the aqueous solution of polyvinyl pyrrolidone is 1 mol / L, the concentration of the sodium hydroxide solution is 2 mol / L, the amount of polyvinyl pyrrolidone in the aqueous solution of polyvinyl pyrrolidone is 0.25 g / mL, and the mass ratio of zinc chloride to polyvinyl pyrrolidone is 1:1.2; in step A3, the mixed solution 1 is added dropwise to the mixed solution 2, and the silane coupling agent KH560 is added thereto, and the mixture is stirred for 20 min to obtain a modified carbon black and zinc oxide composite, and the mass ratio of the silane coupling agent to the carbon black in step A1 is 0.1:16.

[0021] In the preparation process of acrylate-modified nano-silica, hexadecyltrimethylammonium bromide, anhydrous ethanol and ammonia water are added to deionized water at 25°C, stirred for 40 minutes, and then tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and methyl methacrylate mixture are added thereto, stirred at 35°C for 18 hours, centrifuged and dried to obtain the acrylate-modified nano-silica; wherein the amount of hexadecyltrimethylammonium bromide in deionized water is 0.012 g / mL, the volume ratio of deionized water, anhydrous ethanol and ammonia water is 20:60:1, and the mass ratio of hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and methyl methacrylate is 0.2:8:1:4; the centrifugal conditions are: centrifugal rotation speed 1000 rpm for 30 minutes, and the drying conditions are: drying at 30°C in a vacuum drying oven for 6 hours. Example 3

[0022] Compared with Example 1, this embodiment has the following differences, and the rest is referred to Example 1, which is as follows: In the preparation process of tire curing bladder based on nanomaterials, in step S1, chlorinated butyl rubber and modified carbon black and zinc oxide composite are mixed at 110°C for 20 minutes, and the mass ratio of chlorinated butyl rubber to modified carbon black and zinc oxide composite is 45:52; in step S2, the mass ratio of brominated alkylphenol formaldehyde resin to acrylate modified nano-silica is 12:8; in step S3, butyl rubber, modified chlorinated butyl rubber, modified composite resin, magnesium oxide, accelerator are mixed. , softener, scorch retarder and processing aid are mixed at 125°C for 40 minutes, and the mass ratio of butyl rubber, modified chlorobutyl rubber, modified composite resin, magnesium oxide, accelerator, softener, scorch retarder and processing aid is 38:60:25:1.8:3:3:2.4:2; in step S4, the mixed rubber sheet is placed in an injection vulcanizer, the screw temperature is controlled at 85°C, the pressure is controlled at 22MPa, the injection vulcanization temperature is 220°C, and the injection vulcanization is carried out for 45 minutes.

[0023] In the preparation process of the modified carbon black and zinc oxide composite, in step A1, 3-hydroxypyridine is dissolved in isopropanol, carbon black is added, and the mixture is stirred at room temperature for 25 minutes, the amount of 3-hydroxypyridine in isopropanol is 0.22 g / mL, the mass ratio of 3-hydroxypyridine to carbon black is 1:15, and the carbon black is a mixture of carbon black N220 and carbon black N550 in a mass ratio of 1:1; in step A2, the amount of zinc chloride in deionized water is 0.25 g / mL, and the amount of dilute hydrochloric acid is 0. The concentration is 1 mol / L, the concentration of the sodium hydroxide solution is 2 mol / L, the amount of polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is 0.3 g / mL, and the mass ratio of zinc chloride to polyvinyl pyrrolidone is 1:2.2; in step A3, the mixed solution 1 is added dropwise to the mixed solution 2, and then the silane coupling agent KH560 is added thereto, and the mixture is stirred for 30 minutes to obtain a modified carbon black and zinc oxide composite; the mass ratio of the silane coupling agent to the carbon black in step A1 is 0.1:24.

[0024] In the preparation process of acrylate-modified nano-silica, hexadecyltrimethylammonium bromide, anhydrous ethanol and ammonia water are added to deionized water at 35°C, stirred for 60 minutes, and then tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and methyl methacrylate mixture are added thereto, stirred at 45°C for 24 hours, centrifuged and dried to obtain the acrylate-modified nano-silica; wherein the amount of hexadecyltrimethylammonium bromide in deionized water is 0.015 g / mL, the volume ratio of deionized water, anhydrous ethanol and ammonia water is 25:65:1, and the mass ratio of hexadecyltrimethylammonium bromide, tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and methyl methacrylate is 0.6:12:1.5:5; the centrifugal conditions are: centrifugal rotation speed 1500rpm for 40 minutes, and the drying conditions are: drying at 45°C in a vacuum drying oven for 8 hours.

[0025] Comparative Example 1 Compared with Example 1, in this comparative example, in the preparation process of the modified carbon black and zinc oxide composite in step S1, zinc oxide is not generated in situ, and nano zinc oxide is directly added, as follows: The preparation process of the modified carbon black and zinc oxide composite is as follows: 3-hydroxypyridine is dissolved in isopropanol under a nitrogen atmosphere, carbon black is added thereto, nano zinc oxide and silane coupling agent KH550 are added thereto after stirring at room temperature for 18 minutes, and the modified carbon black and zinc oxide composite is obtained after stirring for 25 minutes; wherein, the amount of 3-hydroxypyridine in isopropanol is 0.18 g / mL, the mass ratio of 3-hydroxypyridine to carbon black is 1:12, the carbon black is a mixture of carbon black N220 and carbon black N550 in a mass ratio of 1:1; the mass ratio of carbon black, nano zinc oxide and silane coupling agent is 18:1.2:0.1.

[0026] The rest refer to Example 1 Comparative Example 2 Compared with Example 1, in this comparative example, the carbon black is not modified during the preparation of the carbon black and zinc oxide composite in step S1, as follows: The preparation process of the carbon black and zinc oxide composite is as follows: zinc chloride is added to deionized water, diluted hydrochloric acid is dripped into the solution under stirring to obtain a colorless transparent solution, sodium hydroxide solution is dripped into the solution, the pH value of the solution is adjusted to 8, a white precipitate is obtained, the solution is washed with deionized water, and then mixed with a polyvinyl pyrrolidone aqueous solution, carbon black and a silane coupling agent KH550 are added into the solution, and the carbon black and zinc oxide composite is obtained after stirring for 25 minutes; wherein the amount of zinc chloride in deionized water is 0.22 g / mL, the concentration of diluted hydrochloric acid is 1 mol / L, the concentration of sodium hydroxide solution is 2 mol / L, the amount of polyvinyl pyrrolidone in the polyvinyl pyrrolidone aqueous solution is 0.28 g / mL, and the mass ratio of zinc chloride, polyvinyl pyrrolidone, carbon black and silane coupling agent is 1:1.8:16:0.08.

[0027] The rest is as per Example 1.

[0028] Comparative Example 3 Compared with Example 1, in step S2, the nano-silicon dioxide is not modified, and the nano-silicon dioxide is directly added, as follows: S2. Evenly mix the brominated alkylphenol-formaldehyde resin, acrylate and nano-silica to obtain a modified composite resin, wherein the acrylic resin is methyl methacrylate, and the mass ratio of the brominated alkylphenol-formaldehyde resin, methyl methacrylate and nano-silica is 11:2:5.

[0029] The rest is as per Example 1.

[0030] Comparative Example 4 Compared with Example 1, this comparative example directly adds nano zinc oxide, carbon black and nano silicon dioxide during the preparation of the tire curing bladder, as follows: A method for preparing a tire vulcanization bladder based on nanomaterials comprises the following steps: blending butyl rubber, chlorinated butyl rubber, carbon black, nano zinc oxide, brominated alkylphenol-formaldehyde resin, methyl methacrylate, nano silicon dioxide, magnesium oxide, accelerator, softener, anti-scorch agent and processing aid, kneading at 105°C for 35 minutes, and pressing the mixed film into a sheet after the kneading is completed; placing the mixed film into an injection vulcanizer, controlling the temperature of the screw at 85°C, the pressure at 20MPa, the injection vulcanization temperature at 210°C, and injection vulcanization for 40 minutes to obtain a tire vulcanization bladder; wherein the mass ratio of butyl rubber, chlorinated butyl rubber, carbon black, nano zinc oxide, brominated alkylphenol-formaldehyde resin, methyl methacrylate, nano silicon dioxide, magnesium oxide, accelerator, softener, anti-scorch agent and processing aid is 36:25:25:4:14:2:6:1.5:2.5:2.2:1.8:1.2.

[0031] The rest is as per Example 1.

[0032] Related tests Tear strength test The tear strength test was carried out according to the standard GB / T529-2008. The thin sheet sample was prepared into a sample with a length × width × thickness of 150mm × 20mm × 3mm. A cut of 10mm in length was made with a cutter along the length direction at a width of 10mm. At 25°C, the two sides of the cut of the sample were clamped on the chuck of the CSS-44100 electronic universal testing machine to measure its tear strength.

[0033] Tensile strength and elongation at break test The tensile strength and elongation at break test were carried out according to the standard GB / T1701-2001. The thin sheet sample was cut into dumbbell-shaped specimens with a thickness of 3 mm using a standard specimen cutter. The specimen was clamped in the chuck of a CSS-44100 electronic universal testing machine at 25°C to measure its tensile strength and elongation at break.

[0034] 100%-300% tensile stress test The 300% elongation stress test was carried out according to the standard GB / 528-2009. The thin sheet sample was cut into a dumbbell-shaped sample with a thickness of 2 mm using a standard sample cutter. The sample was clamped in the chuck of the CSS-44100 electronic universal testing machine at 25°C to measure its 300% elongation stress.

[0035] Hardness test The hardness was measured according to the national standard GB / T531-1999 on a Shore A hardness tester produced by Shanghai Xianfeng Film Machinery Factory.

[0036] Use times test Record the number of times the vulcanizing bladder is used under the same conditions.

[0037] The test results are shown in Table 1.

[0038] Table 1 Performance test results

[0039] Aging test The vulcanized bladders prepared in the above embodiments and control examples were subjected to a hot air aging test at a temperature of 120° C. for 120 h. After the aging test, the tensile strength, elongation at break, 300% tensile stress, hardness and number of uses were tested under the same test conditions. The results are shown in Table 2.

[0040] Table 2 Aging performance test

[0041] It can be seen from the test data in Table 1 and Table 2 that the performance of the vulcanization bladders prepared in Examples 1-3 is better than that in Comparative Examples 1-4, and in particular, the test result of Example 1 is the best. This is because the construction of the combination of polyvinyl pyrrolidone-coated zinc hydroxide organic matrix-silane coupling agent-modified carbon black inorganic matrix and the addition of acrylate-modified nano-silica can effectively achieve the dispersion of carbon black, nano-zinc oxide and nano-silica, and the combination containing modified carbon black can be combined with chlorobutyl rubber, and the positively charged pyridine ring contained in the combination and the free chloride ions are aggregated together through positive and negative charges to form an ion cross-linking network, which can effectively improve the mechanical properties of the prepared rubber.

[0042] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0043] Although the embodiments of the present application have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present application, and that the scope of the present application is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a tire curing bladder based on nanomaterials, characterized in that: The following steps are involved: S1. Blending chlorobutyl rubber with modified carbon black and zinc oxide composite, and kneading at 85-110° C. for 10-20 min to obtain modified chlorobutyl rubber; S2, mixing the brominated alkylphenol-formaldehyde resin and the acrylate-modified nano-silica uniformly to obtain a modified composite resin; S3, blending butyl rubber, modified chlorobutyl rubber, modified composite resin, magnesium oxide, accelerator, softener, scorch retarder and processing aid, mixing at 95-125° C. for 20-40 min, and pressing into sheets to obtain mixed rubber sheets after mixing; S4. Put the mixed rubber sheet into an injection vulcanizer, and perform injection vulcanization for 35-45 minutes at 180-220° C. and 18-22 MPa to obtain a tire vulcanization bladder.

2. The method for preparing a tire curing bladder based on nanomaterials according to claim 1, characterized in that: In step S1, the preparation method of the modified carbon black and zinc oxide composite is: A1. Dissolve 3-hydroxypyridine in isopropanol under an inert atmosphere, add carbon black thereto, and stir at room temperature for 15-25 minutes to obtain a mixed solution 1; A2, zinc chloride was added to deionized water, dilute hydrochloric acid was added dropwise under stirring to obtain a colorless transparent solution, sodium hydroxide solution was added thereto, the pH of the solution was adjusted to 8, a white precipitate was obtained, and the precipitate was washed and mixed with a polyvinyl pyrrolidone aqueous solution to obtain a mixed solution 2; A3. Under stirring in an inert atmosphere, add the mixed solution 1 dropwise to the mixed solution 2. After the addition is complete, add a silane coupling agent thereto and stir for 20-30 minutes to obtain a modified carbon black and zinc oxide composite.

3. The method for preparing a tire curing bladder based on nanomaterials according to claim 1, characterized in that: In step S2, the preparation method of acrylate-modified nano-silica is as follows: cetyltrimethylammonium bromide, anhydrous ethanol and aqueous ammonia are added to deionized water at 25-35° C., and after stirring for 40-60 minutes, tetraethyl orthosilicate, bis-[γ-(triethoxysilyl)propyl]-tetrasulfide and a mixture of methyl methacrylate are added thereto, and the mixture is stirred at 35-45° C. for 18-24 hours, and the mixture is obtained after centrifugation and drying.

4. The method for preparing a tire curing bladder based on nanomaterials according to claim 1, characterized in that: In step S3, the accelerator is at least one of accelerator DM and accelerator ZDC, the softener is sulphurized cottonseed oil, the scorch retarder is PVI, and the processing aid is stearic acid.

5. The method for preparing a tire curing bladder based on nanomaterials according to claim 2, characterized in that: In step A1, the carbon black is at least one of carbon black N220 and carbon black N550.

6. The method for preparing a nanomaterial-based tire curing bladder according to claim 2, characterized in that: In step A3, the silane coupling agent is at least one of KH550, KH560, and KH570.

7. The method for preparing a tire curing bladder based on nanomaterials according to claim 2, characterized in that: The drying conditions are: drying in a vacuum drying oven at 30-45°C for 6-8h.

8. A tire curing bladder based on nanomaterials, characterized in that: The tire curing bladder is prepared by the method for preparing a nanomaterial-based tire curing bladder as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Low zinc rubber composition

    CN109369994A

  • Preparation method of tire curing bladder

    CN110684293A

  • Preparation method and application of anti-ultraviolet dendritic silicon dioxide nanomaterial

    CN113735129A

  • Long-life tire curing bladder and preparation method thereof

    CN116285130A

Cited By

  • Resin aid for tire rubber material, tire rubber material, preparation method and tire

    CN119350773A